Analisis Strategi Komunikasi Pemasaran Terpadu dalam Meningkatan Partisipasi Pemilih pada Pemilu 2014 - Wira Respati (Bina Nusantara University, 2015)
As the institution in charge of election administration, Election Commission of Republic of Indonesia or Komisi Pemilihan Umum (KPU) has consistently conducted campaign to increase number of voters who will participate in election. As a matter of fact, result of previous elections showed how the level of participation has been decreased. Lack of political awareness, level of knowledge upon the importance of election as well as skepticism on government and representatives’ performance were believed to be the trigger. Hence, it is important for KPU to enhance effective marketing communication program, ranging from the stages of planning, implementation and evaluation to promote public awareness to participate in the election. Therefore, this study aims to find how the principles of social marketing are actually implemented in designing communication program to increase voter awareness upon the importance of 2014 election. This study used qualitative method. Data were gathered from interview with related parties and literature study. Research found that the principles of social marketing to build awareness of voters basically have already been integrated in the programs of KPU toward the entire group of voters. In addition, KPU is quite aware of the importance of synergy between the programs of their communications both above the line and below the line. On April 9th legislative election, level of participation were increasing, reached 75.11%, up from 71% in the previous 2009 election. However, the level of participation of the July 9th presidential election dropped to 70% compared to the previous election in 2009, 72%. The result of these two elections should be considered as another challenge to KPU in improving their marketing communication strategy in the future.